Towards One CGIAR: CCAFS' contribution to integrating the work of CGIAR - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Meeting the challenges posed by the impacts of climate change to agriculture in developing countries is central to achieving CGIAR goals. These challenges cut across the entire range of centers’ and CRPs’ expertise; they are not amenable to solution by any single institution. Since its inception in 2011, CCAFS has been bringing together multiple CGIAR centers and CRPs to address this challenge. It has also reached beyond those centers that are formal CCAFS partners. The purpose has been to move beyond single-Center projects to integrating the work of multiple Centers in a way that creates significant synergies. This report selectively highlights CCAFS’ most important achievements in crossCGIAR integration as of late 2020.